DEMAND FOR DIFFERENTIATED DURABLE PRODUCTS: THE CASE OF THE U.S. COMPUTER PRINTER MARKET. - MELNIKOV, OLEG (Economic Inquiry, 2013)
This paper develops an estimation technique for analyzing the impact of technological change on the dynamics of consumer demand in a differentiated durable products industry. The paper presents a dynamic model of consumer demand for differentiated durable products that explicitly accounts for consumers' expectations of future product quality and consumers' outflow from the market that arises endogenously from their purchase decisions. The timing of consumers' purchases is formalized as an optimal stopping problem. A solution to that problem defines the hazard rate of product adoptions, while the nested discrete choice model determines the alternative-specific purchase probabilities. Integrating individual decisions over the population distribution generates rich dynamics of aggregate and product-level sales. The empirical part of the paper applies the model to data on the U.S. computer printer market for 1998-1999. The estimates support the hypothesis of consumers' forward-looking behavior, allowing for better demand forecasts and improved measures of welfare gains from introducing new products. ( JEL L11, C35, D91)